Antibiotic resistance pattern of bacteria isolated from various clinical specimens: an eastern Indian study - Paul, Rudrajit; Ray, Jayanti; Sinha, Sourav; Mondal, Jayati (International Journal Of Community Medicine And Public Health, 2017)
Background: Resistance to antibiotics is an extremely common phenomenon in bacteria isolated from clinical material. This is a serious threat to patient care all over the world. In India, antibiotic resistance has far reaching public health consequences. In this observational study, we aimed to generate data on the prevailing pattern of antibiotic resistance from Eastern India. Methods: This was a hospital based study involving both indoor and outdoor patients. Patients with history of antibiotic use in the past 3 months were excluded. The clinical specimens (blood, urine, pus etc.) were incubated for up to 7 days under aerobic conditions before declaring them as negative. Antibiotic sensitivity was tested by modified Kirby-Bauer disc diffusion method according to CLSI guidelines. Results: There were a total of 93 specimens with the majority being blood culture (n=43) and urine (n=33). Majority (n=57; 61.3%) of isolated organisms were gram negative with E. coli predominating (n=36). Of the gram-positive isolates, Staphylococcus predominated (32 out of 36). 100% of isolates from urine were gram negative while for blood, 60% of the isolates were gram positive. Resistance to penicillin group and cotrimoxazole was up to 100% in certain species. For carbapenem group, resistance varied from 17 to 75%. Resistance to aminoglycosides was 75% in Pseudomonas and 85% in Klebsiella. Conclusions: Our study has demonstrated very high levels of resistance to different common antibiotics in different classes of bacteria. Such data can be used for antibiotic stewardship and also to formulate antibiotic use protocols.